(untitled) (Research, Society and Development, 2020)
The ingestive behavior study is an important tool for diet evaluation and the relationship of the animal with production system. The objective this study was to analyze the ingestive behavior of cattle in grazing and feedlot for some variables, under experimental conditions. Scientific papers published from September 2004 to March 2018 were analyzed using the systematic review framework. Of the 88 papers initially selected, after applying new selection criteria, 35 articles constituted the information bank, with 153 information and 1079 cattle in experiments. The study showed statistical difference (P <0.0001) to analyzed parameters between cattle production systems. The average time found, in minutes per day, for feeding was higher in pasture systems (520.13) than in confined systems (249.39). The time spent by animals in rumination and idle was greater in confined systems (470.28 and 691.86, respectively) than in pasture (319.21 and 360.50, respectively). The production systems have an influence on the ingestive behavior of cattle. The production systems meddle the ingestive behavior of cattle. However, a diet used in different production systems was main responsible for the change in the behavior of animals, proving to be important to advance studies on the topic.